Shelf-life and labels: A cheap dating tool for seafloor macro litter? Insights from MEDITS surveys in Sardinian sea. (April 2019) - Cau, Alessandro; Bellodi, Andrea; Moccia, Davide; Mulas, Antonello; Porcu, Cristina; Pusceddu, Antonio; Follesa, Maria Cristina
Abstract: The global plastic economy demands to reduce the flow of plastic into oceans and promote remedial actions for already accumulated seafloor litter. In this perspective, baseline levels of contamination and tools for dating litter items in order to assess the efficacy of those actions, are thus needed. In this note we discuss the utility of introducing the acquisition of shelf-life and labels features from litter items into already established standardized protocols such as the one proposed by MEDiterranean International Trawl Survey (MEDITS). Our investigation was conducted on 612 high resolution images of litter items collected in each haul, which was retrieved during 6 years of surveys (2013–2018) around Sardinian sea (central western Mediterranean). While for the majority of items (89%) expiration date or labels were not present or legible, over 50% of dated items were likely dumped at sea from a period <5 years. In this perspective, this sort of data could represent a useful tool for monitoring the effectiveness of input reduction actions that implicitly rely on the gradual reduction of recently dumped items. Highlights: Tools for estimating the efficacy of measures aimed at reducing the input of litter in worlds' oceans are needed. Expiration dates and label features were retrieved from MEDITS survey photo material from 2013 to 2018 in order to back date seafloor macro-litter items. A total of 54 items were back dated, including aluminum cans produced in 1980's. Plastic items dumped within 5 years from retrieval are the most numerous and identifiable seafloor macro-litter items. This practice could be introduced in operation onboard to monitor the redution of this fraction of seafloor litter across years and thus the efficacy of input reduction measures.